2016
DOI: 10.1007/s10549-016-3695-1
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer screening using tomosynthesis in combination with digital mammography compared to digital mammography alone: a cohort study within the PROSPR consortium

Abstract: Purpose Digital breast tomosynthesis (DBT) is emerging as the new standard of care for breast cancer screening based on improved cancer detection coupled with reductions in recall compared to screening with digital mammography (DM) alone. However, many prior studies lack follow-up data to assess false negatives examinations. The purpose of this study is to assess if DBT is associated with improved screening outcomes based on follow-up data from tumor registries or pathology. Methods Retrospective analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
100
2
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 164 publications
(120 citation statements)
references
References 16 publications
(14 reference statements)
8
100
2
6
Order By: Relevance
“…Our study confirmed the results obtained in previous studies [5,25,26]; there was an increase in both true-negative and true-positive cases with DM+DBT compared to DM alone.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our study confirmed the results obtained in previous studies [5,25,26]; there was an increase in both true-negative and true-positive cases with DM+DBT compared to DM alone.…”
Section: Discussionsupporting
confidence: 92%
“…More cases were also classified BI-RADS category 4 and 5 with DBT+DM (about 13% more than with DM alone), which means higher cancer detection rates, consistent with the results of prior studies [29,30]. There was also a significant reduction in false-positive and false-negative cases as also previously reported in the literature [20,25]. The work-up rate was significantly reduced with DBT+DM versus DM alone (33-42%), similar to previous studies in analogue settings (38.5% for 1-view tomosynthesis [24]).…”
Section: Discussionsupporting
confidence: 90%
“…DBT imaging was added to the practice in September 2011. Our institution previously published results that compared the digital mammography/DBT group with 10 728 patients from a digital mammographyonly screening population (2,3,(16)(17)(18)(19).…”
Section: Dose Calculationsmentioning
confidence: 99%
“…Other studies corroborated these findings. 43,44 Some points are yet to be discussed regarding the tomosynthesis protocol. The Food and Drug Administration recommends a combined approach (combo mode) to breast cancer screening, in which conventional digital mammography views (mediolateral-oblique and cranial-caudal) are combined with tomosynthesis acquisition in those same two planes.…”
Section: Considerations Regarding Breast Tomosynthesismentioning
confidence: 99%